Effects of the installation of offshore pipelines on macrozoobenthic communities (northern and central Adriatic Sea). (January 2019) - Spagnolo, A.; Cuicchi, C.; De Biasi, A.M.; Ferrà, C.; Montagnini, L.; Punzo, E.; Salvalaggio, V.; Santelli, A.; Strafella, P.; Fabi, G.
Abstract: Macrozoobenthos living around several pipelines placed at different depths and sediment types in the Western Adriatic Sea was investigated for three years after structures' deployment to detect possible effects due to their installation and presence. Three environmental habitats were considered based on the grain size (silty clay, clayey silt and sand). Samplings were taken within a radius of 100 m from the pipelines and at control sites. Multivariate and univariate analysis showed peculiarities of the three habitats due to the different sediment type, without differences between pipelines and controls inside each group. Silty clay and clayey silt communities appeared quite similar, being mainly represented by opportunistic species typical of the Adriatic coastal area. Benthic populations found at the offshore relict sand were characterized by a higher percentage of sensitive species. Independently of sediment typology, pipelines' installation seems to not affect the benthic populations that appear more influenced by environmental features. Highlights: Seven pipelines were investigated to detect their effects on macrozoobenthos. Three types of sediment were considered (sand, silty clay and clayey silt). Silty clay and clayey silt communities were similar (mainly opportunists). Sand community was mainly composed by sensitive species. Benthic communities appear influenced by environmental features.